Os anglicismos em sala de aula: Uma proposta de trabalho para o ensino fundamental a partir de gêneros jornalísticos - Freitas, Andressa Bezerra Cirqueira (Universidade Federal do Tocantins, 2022)
The expansion of the lexicon is a natural process, since the language is constantly changing and new creations appear and adapt to the speaker's reality. New lexical units have been introduced to the Portuguese language over the years, including anglicisms, words from the English language, which are common in our country. Considering that this recurrence reaches the textual genres approached at school, we seek to elaborate, apply and analyze a work proposal with anglicisms having as main focus the work with the journalistic textual genres and the use of the dictionary in a 9th grade class of Elementary School . In addition, this research seeks to present the reasons for the occurrence of foreigners in English being greater than in other languages, pointing out whether they are economic, social, cultural. The choice of the journalistic medium was due to the fact that it is always up to date, sharing recent information and, naturally, this characteristic is reflected in the language used. The research method that supports this work is qualitative and interventional and will try to outline some answers, which are not definitive, but can help to reconstruct the mediation of the teacher in the study of foreign words in the classroom, thus helping in the teaching and learning process, in addition to deconstructing paradigms regarding the use of the dictionary in school life.